2013
DOI: 10.1161/atvbaha.112.301006
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus Limits Aortic Aneurysm in the Apolipoprotein E–Deficient Mouse by Downregulating C-C Chemokine Receptor 2 Positive Monocytes

Abstract: Objective-We aimed to determine the effect of mechanistic target of rapamycin inhibitor everolimus on abdominal aortic aneurysm within the angiotensin II (A2)-infused apolipoprotein E-deficient mouse model. Approach and Results-Abdominal aortic aneurysm was induced via subcutaneous infusion of A2. Flow cytometry demonstrated increased circulating and aortic C-C chemokine receptor 2 (CCR2) monocytes during A2 infusion. The number of CCR2 monocytes present within the aorta was positively correlated with supraren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…The precise benefits of rapamycin in this setting require further definition, but may relate to effects on SMC cytoskeleton organization besides its antiproliferative properties (40). Inhibition of mTOR signaling in vascular cells represents what we believe is a novel therapeutic approach to preventing aortic disease, although additional work is required to exclude an immunosuppressive effect as the relevant mechanism (41,42). However, a concern against the use of cytostatic agents is that fibroblast hyperplasia and adventitial thickening contribute to vessel wall integrity and may prevent fatal transmural rupture.…”
Section: Discussionmentioning
confidence: 99%
“…The precise benefits of rapamycin in this setting require further definition, but may relate to effects on SMC cytoskeleton organization besides its antiproliferative properties (40). Inhibition of mTOR signaling in vascular cells represents what we believe is a novel therapeutic approach to preventing aortic disease, although additional work is required to exclude an immunosuppressive effect as the relevant mechanism (41,42). However, a concern against the use of cytostatic agents is that fibroblast hyperplasia and adventitial thickening contribute to vessel wall integrity and may prevent fatal transmural rupture.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that AngII infusion increased inflammatory mature monocytes, which differentiate into M1 macrophage in the bloodstream. 42 Both EPA and DHA may have the potential to inhibit AAA development by reducing the number of inflammatory monocytes. We assessed the inhibitory effects of ω3-PUFAs on early changes in the aorta after 5 days of AngII infusion, as per Study Protocol 1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent data suggest that everolimus, an mTOR inhibitor, attenuated M1 polarization in ApoE -/-BMDMs in vitro and AAA formation in vivo. [35] The choice of BMDM as an in vitro model for changes observed in the intact suprarenal aorta is complicated by a recent bone marrow transplant study in which donor marrow from cholesterol fed LDLR -/-…”
Section: Tlr4mentioning
confidence: 99%